The diagnostic ability of peripapillary vessel density in primary open-angle glaucoma suspects - Lifang Liu; Yongdong Lin; Xiaoqin Xie; Jie Peng; Chukai Huang; Di Ma; Mingzhi Zhang (Photodiagnosis and Photodynamic Therapy)
Objective: To assess the diagnostic ability of peripapillary vessel density (pVD) in primary open-angle glaucoma suspect (GS) patients. Methods: Sixteen primary open-angle GS patients (22 eyes) and 20 normal controls (22 eyes) were included. In the GS group, OCTA measurements of pVD (superior, inferior, nasal, temporal, and global), OCT measurements of retinal nerve fiber layer (RNFL) thickness, disc area, rim area and ganglion cell complex (GCC) thickness were examined. In the control group, pVD measurements were performed. The vessel density between the two groups was compared. The correlation between OCTA and OCT parameters was evaluated. The receiver operating characteristic curve (ROC) was used to evaluate the diagnostic efficacy of OCTA measurements. Results: The global (P < 0.001), nasal (P = 0.003), and inferior (P = 0.002) quadrant pVD in GS group was considerably lower than the control group. The global pVD was positively correlated with the inferior RNFL thickness (r = 0.492, P = 0.023) and rim area (r = 0.483, P = 0.027). The inferior pVD was positively correlated with the inferior RNFL thickness (r = 0.648, P = 0.001), the nasal RNFL thickness (r = 0.441, P = 0.045), the rim area (r = 0.439, P = 0.046) and the GCC thickness (r = 0.472, P = 0.048). The global pVD had the best diagnostic value (AUC=0.825, sensitivity 86.36 %, specificity 72.73 %, cutoff value 45 %), followed by the inferior (AUC=0.749) and nasal (AUC=0.748) quadrant pVD. Conclusion: In primary open-angle GS patients, the global and inferior quadrant pVD was lower than that of normal people, and it was positively correlated with the inferior RNFL thickness and rim area. The diagnostic value of pVD for discriminating GS from normal people was excellent with high sensitivity and specificity.